Measuring nutritional dimensions of household food security: Technical guide: strengthening the household food security and nutritional aspects of IFAD poverty alleviation projects: developing operational methodologies for project design and monitoring - Morris, Saul Sutkover (International Food Policy Research Institute, 1999)
This guide outlines methodologies that will assist practitioners to improve the nutrition impact of development activities. The methodologies described here are jointly referred to as nutritional assessment. The guide begins by explaining what is meant by nutritional assessment, and how it can reinforce linkages between nutrition and agricultural development. The guide then considers how nutritional assessment can be used in rural development projects for beneficiary targeting and project formulation, as well as for practical project monitoring and evaluation. It is concluded that nutritional assessment has great potential for geographical targeting at little additional cost, and is also a useful input into project formulation. It is invaluable at the monitoring and evaluation stage because it offers the possibility of directly measuring the human welfare impact of development activities, and also because the information generated can only with some difficulty be manipulated by interested parties. In the final section of the guide, the preceding theoretical discussions are illustrated using data from Honduras and Northern Ghana.